Sleeping tablet consumption, self reported quality of sleep, and working conditions. Group of Occupational Physicians of APSAT. Issue 1 (February 1993) - Jacquinet-Salord, M C; Lang, T; Fouriaud, C; Nicoulet, I; Bingham, A
Abstract : STUDY OBJECTIVE--The aim was to assess the frequency of sleep disorders in relation to working conditions. DESIGN--This was a cross sectional study. Data were collected prospectively, on a standardised form, by 13 occupational physicians. The quality of sleep was assessed by self perceived sleep disturbances and consumption of sleeping tablets. Working conditions were described by the worksite physician as well as by the participants. SETTING--2769 small or medium sized firms in the Paris area. PARTICIPANTS--A random sample of 7629 wage earners was studied. Among the participants, 61% were men and 39% women; 44% were blue collar workers. MAIN RESULTS--The prevalence of sleeping tablet consumption was 6.1% and 11.3% respectively for men and women. Sixteen percent of men and 26% of women stated that they had sleep disturbances (p < 0.001). In both sexes, drug consumption and sleep disturbances increased with age and were highest among individuals aged 55 years and more. No association between working conditions (exposure to noise, assembly line working, or physical workload) and sleep disturbances or drug consumption was found. Sleeping tablet consumption was higher among subjects reporting a bad atmosphere at work; the same was true for men with little interest in their job and for women working under time pressure. For both sexes, subjects reporting any of these conditions were more likely to report sleep disturbances. CONCLUSIONS--A high prevalence of self reported sleep problems and related drug consumption was observed. Physical working conditions were not related to the quality of sleep in contrast to perceived job conditions. The results suggest that sleep quality might be a useful health indicator for the occupational physician.